(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of Siamese Orange Marketing System in Taro Village, Tegallalang District, Gianyar Regency. Siamese oranges (Citrus nobilis var. microcarpa) are horticultural plants that are of concern to the government and the public. This subsector is expected to be able to increase the production and welfare of farmers achieved through efforts to increase income, production, and business productivity. This research aims to find out the marketing channels and marketing functions performed by marketing agencies on siamese citrus commodities in Taro Village and the efficiency of siamese orange marketing channels based on marketing margins, farmer’s share, and profit and cost ratios. The research site was conducted in Taro Village, Tegallalang District, Gianyar Regency. The data used in this study uses primary data and secondary data. The results of this study showed three marketing channels, marketing functions consist of exchange functions, physical functions, and facility functions. The most efficient marketing channel is found in channel l, because of the low marketing margin, farmer’s share is high as well as the ratio of profit and cost more than one (>1). For grade A the amount of marketing margin is Rp. 2,500, farmer’s share of 75%, and total analysis of profit and cost ratio of 1.44. For grade B the amount of marketing margin is Rp. 1,500, farmer’s share of 81%, and total analysis of profit and cost ratio of 1.31. For grade C the amount of marketing margin is Rp. 2,500, the farmer’s share is 58% and the total profit and cost ratio analysis is 2.37. Based on the results of the study, it is expected that farmers can directly sell siamese oranges both to retailers and to end consumers and can form cooperatives.